Regularization of distributions - Ricardo Estrada (International Journal of Mathematics and Mathematical Sciences, 1998)
We give a simple necessary and sufficient condition for the existence of distributional regularizations. Our results apply to functions and distributions defined in the complement of a point, in one or several variables. We also consider functions defined in the complement of a hypersurface. We apply these results to the existence of distributional boundary values of harmonic and analytic functions.